Kajian Konsentrasi Gelatin dan Sirup Glukosa Terhadap Mutu Sensori Permen Jelly Nira Batang Kelapa Sawit Tua (Elaeis guineensis Jacq) - Siti Nurdjanah; Alif Fikri Nur Hidayat; Udin Hasanudin (JURNAL AGROINDUSTRI HALAL, 2025)
Old palm oil palm sap contains an appreciable amount of sugar. An alternatif to utilize the sap from old palm trunks is to process into jelly candy. This research was aimed to determine the right formulation of gelatin and glucose sugar to produce jelly candy made from palm tree sap with the best sensory quality and chemical properties. The research was carried out as a non-factorial, arranged in a Completely Randomized Design (CRD) with 5 replications. The experiment was conducted through two stages. The first stage was the addition of gelatin concentration of 2%, 3%, 4%, 5% and 6% with glucose syrup of 10 %. The best result from the first stage was then continued to find the best concentration of glucose syrup at 0%, 2.5%, 5%, 7.5% and 10% in the second stage. The test results show that the best gelatin concentration was 6%. In the second stage, the best glucose syrup concentration was 2.5%.